Pengaruh Persistensi Laba dan Laba Negatif Terhadap Koefisien Respon Laba dan Koefisien Respon Nilai Buku Ekuitas pada Perusahaan Manufaktur di Bursa Efek Jakarta - Zahroh Naimah; Sidharta Utama (The Indonesian Journal of Accounting Research, 2013)
The objective of this study is to examine the value relevance of accounting earnings and book value of equity in explaining stock price. The study is aimed to identify the factors that influence earnings response coefficient and equity book value coefficients. The factors are negative earnings and earnings persistence. The results show that accounting earnings and book value of equity are positively associated with stock price. This results support the prior studies that accounting earnings and book value of equity have value relevance (Ohlson, 1995; Burgthaler and Dichev, 1997, etc). Accounting earnings and book value of equity are useful to explain stock price changes. The results of this study are consistent with previous studies that earnings response coefficient is greater in the firms that have permanent earnings (Ohlson, 1995; Collins and Kothari, 1989; Barth et al., 1998; Ou and Sepe, 2002), According to prior studies, earnings response coefficient is smaller in the firms that have negative earnings (Jan and Ou, 1995; Hayn, 1995). Book value response coefficients is smaller in the firms that have permanent earnings and greater in the firms that have negative earnings, consistent with Ohlson, 1995; Collins and Kothari, 1989; Barth et al., 1998; Ou and Sepe, 2002, Jan and Ou, 1995; Hayn, 1995.